Facilitators and challenges in collaboration between public health units and faith-based organizations to promote COVID-19 vaccine confidence in Ontario - Kadidiatou Kadio; Denessia Blake-Hepburn; Melodie Yunju Song; Anna Karbasi; Elizabeth Estey Noad; Samiya Abdi; Nazia Peer; Shaza A. Fadel; Sara Allin; Anushka Ataullahjan; Erica Di Ruggiero (International Journal for Equity in Health)
Abstract Background Equitable access to vaccination remains a concern, particularly among population groups made structurally vulnerable. These population groups reflect the diversity of communities that are confronted with structural barriers caused by systemic racism and oppression and result in them experiencing suffer disadvantage and discrimination based on citizenship, race, ethnicity, ancestry, religion, spiritual beliefs, and/or gender identity. In Canada, Ontario public health units (PHUs) engage with faith-based organizations (FBOs) to improve vaccine confidence among populations made structurally vulnerable. This study explores the factors that facilitate and hinder engagement in the implementation of vaccine confidence promoting interventions, and challenges associated with working with FBOs. Methods In-depth interviews were conducted with 18 of the 34 Ontario PHUs who expressed an interest. Braun and Clarke’s “experiential” approach was used to explore the realities of PHUs’ contextual experiences and perspectives. Results The results showed that receptivity and openness of PHUs to learn from FBOs, previous experience working with religious communities and FBOs, ongoing relations based on respect of different beliefs and opinions on the vaccines, leveraging the support of trusted faith leaders among communities and communications strategy adapted and sensitive to the needs of the community was facilitators to community involvement in the prevention and control of COVID-19. On the other hand, factors both internal and external to the PHUs have often posed challenges to collaboration with the FBOs. Internal factors include low operational capacity of PHU like insufficient human and financial resources, weak analytical capacity, ambiguity in the roles and responsibilities of the different actors. Some external challenges issues were related to the provincial level and the Ministry of Health, while others were related to FBOs. For example, faith-based and collective beliefs promoting vaccine hesitancy have resulted in resistance from some religious communities when PHUs have reached out to collaborate. Conclusions Engaging with faith-based communities is an ongoing process that requires time, flexibility, and patience, but it is necessary to improve vaccine confidence and equity access among population groups made structurally vulnerable. Lessons learned from this research can guide the implementation of future vaccination programs.